Implementasi Penilaian Kurikulum 2013 pada Bidang Studi Pendidikan Agama Islam di SMA Negeri Kota Tenggarong - Firdan, Firdan (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2017)
This research is grounded by the low understanding of the assessment in the Curriculum 2013 is one of the problems in school. This is due to internal and external barriers. To overcome these obstacles it is necessary to have quality coordination from the competent party with the school related to the implementation of the 2013 curriculum assessment. This study aims to determine the implementation of the 2013 curriculum assessment model and the supporting and inhibiting factors of the implementation of the 2013 curriculum assessment model, especially the field of Islamic Religious Education study at Tenggarong high school. The research method used qualitative descriptive type with multi disciplinary approach. While processing techniques and data analysis using data reduction, data presentation and drawing conclusions. The result of this research is the implementation of curriculum 2013 assessment the field of Islamic Religious Education Studies at Tenggarong High School covers four aspects, namely, spiritual aspect, knowledge aspect, social aspect and skill aspect that has been implemented. In detail can be concluded as follows: 1) Assessment based on the type used is Daily Deuteronomy in writing and oral, assignment, Mid Semester and Deuteronomy end of semester, but not yet executing authentic assessment model. 2) Appraisal Assessment based on the aspects used are observations, in attitude assessment, both spiritual and religious attitudes, but have not used self-assessment, assessment among friends, journal notes teachers. While the skills aspect has not used project appraisal and portopolio. 3) Supporting and inhibiting factors in implementing the curriculum 2013 assessment in the field of study of Islamic Religious Education at State Senior High School 1 and State Senior High School 2 in Tenggarong show similarity. From the spiritual aspect, social aspect, knowledge aspect and skill aspect. While the inhibiting factor is the inadequate allocation of learning time of Islamic Religious Education, the difficulty of making indicators of spiritual attitudes and social attitudes to be assessed, the questions tested have not been tested yet, the limitations of the means of worship, the condition of the less disciplined students, the assessment of the practice exam is not conducive, The lack of involvement of other teachers in the assessment of spiritual attitudes and social attitudes.